A Flower Beetle, Euphoria sepulcralis (Fabricius) (Insecta: Coleoptera: Scarabaeidae) - Michael C. Thomas (EDIS)
EENY-416, a 4-page illustrated fact sheet by Michael C. Thomas, is part of the Featured Creatures collection. It describes this day-flying scarab beetle common in Florida and the eastern U.S., its synonymy, distribution, identification, biology, hosts, pest status, and management. Includes selected references. Published by the UF Department of Entomology and Nematology, September 2007.